TINGKAT PARTISIPASI MAHASISWA DALAM PERKULIAHAN ELEARNING MELALUI FORUM DISKUSI DI PGSD FKIP UNSYIAH - Mislinawati .; Suci Fitriani (Jurnal Pesona Dasar, 2020)
One of the demands of universities today is to implement an online learning system. During the pandemic, all activities are carried out online, including lecture activities. Based on observations during learning during the pandemic, especially in the odd semester of 2020/2021, many lecturers implemented e-learning, from 30% to 85%, this was a very significant increase. This also had a significant effect on students, especially the level of participation in lectures increased. Student participation has an important role in learning success. The active participation of students is able to achieve learning goals so that academic achievement increases. Discussion forums are a vehicle for students to develop ideas and thoughts. From the results of the observation the discussion forum can increase their participation in the discussion, it can even trigger them to give their opinion so that students have confidence in conveying their ideas. This forum also provides space and flexibility so that all students actively participate in lectures. The student participation rate in e-learning courses reaches 90% of each topic discussed.